ANALISIS BUKU FISIKA SMA KELAS XII MATERI LISTRIK DINAMIS BERDASARKAN ASPEK KONSEPTUAL DAN PROSEDURAL - Ari, Hilarius Donatus Hun; Fakhruddin, Fakhruddin; Yusuf, Yusniati H. Muh (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2019)
This research aims to determine the availability of aspects of conceptual knowledge and procedural knowledge in the textbooks of high school physics class XII curriculum 2013 on dynamic electrical staple material. This study uses a qualitative approach with evaluative types. The study was conducted at SMA Negeri 2 Kupang, SMA Negeri 4 Kupang, SMA Negeri 5 Kupang, SMA Negeri 8 Kupang, and MA Negeri Kupang. The results showed that the availability of conceptual knowledge in textbooks A amounted to 59.03% (High category) and textbook B of 60.43% (High category). The availability of A procedural knowledge aspect of textbook A is 13.89% (Low category) and textbook B of 15.75% (Low category).